Tinjauan Hukum Kedudukan dan Keterlibatan Kearifan Lokal Masyarakat Adat Maluku Berupa Sasi dalam Pengelolaan Lingkungan Hidup - Alvayedo, Muhammad Brillyan; Erliyana, Anna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Indigenous peoples in Maluku Archipelago have a method to conserve natural resources in the form of local wisdom called Sasi. Sasi is an environmental management and the preservation of natural resources on the land and at the sea which conducted by the indigenous people of Maluku. The broad scope of Sasi is an activity that prohibits the taking of certain potential products without damaging the environment. Besides law and regulations that regulated by the government in Article 32 of 2009 about Environmental Management and Preservation, there is a Sasi customary law which also regulating about the utilization and environmental management of natural resources. With the result that the presence of local wisdom increasingly emphasized that Sasi is involved in environmental management at the Maluku Archipelago.